KONSEP PENAMAAN PADA RUANG PUBLIK DI KOTA MANOKWARI: KAJIAN LANSKAP LINGUISTIK - PARADIDA, YULIA PUTRI (Universitas Galuh, 2024)
This research uses a Landscape Linguistic approach to understand the concept of naming in public spaces in West Papua Province, specifically in Manokwari City. This research uses a qualitative descriptive method, where researchers directly describe the concept of naming in public spaces in Manokwari City, West Papua Province, using the theoretical framework of the Linguistic Landscape. Data collection techniques involve observation and interviews, while data analysis involves presenting and analyzing data after the data has been collected. The research results show that naming concepts can be classified according to the information function contained in naming streets, offices, cafes and places to eat based on historical factors, expectations and agreements. Meanwhile, based on the symbolic function of street signs, there are elements of power relations, cultural relations and language policies. There are elements of language policy and language status on the office sign. The signs on cafes and eating places reflect aspects of language imperialization.